Partie de l'Amérique septent? qui comprend la Nouvelle France ou le Canada - Robert de Vaugondy, Gilles, 1688-1766 ([Paris], 1793)
Hand coloured. Decorative title cartouche by Groux (named at bottom left edge). Relief shown pictorially. Bar scales in "mille pas géométriques" and marine leagues. -- Inset: Supplement pour les lacs du Canada. 20.6 x 35.9 cm. CNS map no. 198. Leaf number on verso: 108.